Mesenchymal stem cell-derived exosome and liposome hybrids as transfection nanocarriers of Cas9-GFP plasmid to HEK293T cells - Behnaz Gharehchelou; Mehrnoush Mehrarya; Yahya Sefidbakht; Vuk Uskoković; Fatemeh Suri; Sareh Arjmand; Farnaz Maghami; Seyed Omid Ranaei Siadat; Saeed Karima; Massoud Vosough (PLoS ONE, 2025)
Exosomes are natural membrane-enclosed nanovesicles (30–150 nm) involved in cell-cell communication. Recently, they have garnered considerable interest as nanocarriers for the controlled transfer of therapeutic agents to cells. Here, exosomes were derived from bone marrow mesenchymal stem cells using three different isolation methods. Relative to filtration and spin column condensation, the size exclusion chromatography led to the isolation of exosomes with the highest purity. These exosomes were then hybridized with liposomes using freeze-thaw cycles and direct mixing techniques to evaluate whether this combination enhances the transfection efficiency of large plasmids. The efficiency of these hybrids in transferring the Cas9-green fluorescent protein plasmid (pCas9-GFP) into the human embryonic kidney 293T (HEK293T) cells was evaluated compared to the pure exosomes. Both Cas9-GFP-loaded exosomes and exosome-liposome hybrids were taken up well by the HEK293T cells and were able to transfect them with their plasmid loads. Meanwhile, the treatment of the cells with plasmids alone, without any vesicles, resulted in no transfection, indicating that the exosome and exosome-liposome hybrids are essential for the transfer of the plasmids across the cell membrane. The pure exosomes and the hybrids incorporating liposomes obtained by the heating method transfected the cells more efficiently than those containing liposomes obtained by the thin film hydration technique. Interestingly, the method of combining exosomes with liposomes (freeze-thaw vs. direct mixing) proved to be more decisive in determining the size of the vesicular hybrid than their composition. In contrast, the liposome component in the hybrids proved to be decisive for determining the transfection efficiency.